Developing a National Trauma Research Action Plan: Results from the prehospital and mass casualty research Delphi survey. Issue 2 (February 2022) - Newgard, Craig D.; Braverman, Maxwell A.; Phuong, Jimmy; Shipper, Edward S.; Price, Michelle A.; Bixby, Pamela J.; Goralnick, Eric; Daya, Mohamud R.; Lerner, E. Brooke; Guyette, Francis X.; Rowell, Susan; Doucet, Jay; et al.
Abstract : BACKGROUND: The National Academies of Sciences, Engineering, and Medicine 2016 trauma system report recommended a National Trauma Research Action Plan to strengthen and guide future trauma research. To address this recommendation, 11 expert panels completed a Delphi survey process to create a comprehensive research agenda, spanning the continuum of trauma care. We describe the gap analysis and high-priority research questions generated from the National Trauma Research Action Plan panel on prehospital and mass casualty trauma care. METHODS: We recruited interdisciplinary national experts to identify gaps in the prehospital and mass casualty trauma evidence base and generate prioritized research questions using a consensus-driven Delphi survey approach. We included military and civilian representatives. Panelists were encouraged to use the Patient/Population, Intervention, Compare/Control, and Outcome format to generate research questions. We conducted four Delphi rounds in which participants generated key research questions and then prioritized the questions on a 9-point Likert scale to low-, medium-, and high-priority items. We defined consensus as ≥60% agreement on the priority category and coded research questions using a taxonomy of 118 research concepts in 9 categories. RESULTS: Thirty-one interdisciplinary subject matter experts generated 490 research questions, of which 433 (88%) reached consensus on priority. The rankings of the 433 questions were as follows: 81 (19%) high priority, 339 (78%) medium priority, and 13 (3%) low priority. Among the 81 high-priority questions, there were 46 taxonomy concepts, including health systems of care (36 questions), interventional clinical trials and comparative effectiveness (32 questions), mortality as an outcome (30 questions), prehospital time/transport mode/level of responder (24 questions), system benchmarks (17 questions), and fluid/blood product resuscitation (17 questions). CONCLUSION: This Delphi gap analysis of prehospital and mass casualty care identified 81 high-priority research questions to guide investigators and funding agencies for future trauma research. Abstract : We used a Delphi process and interdisciplinary national experts in prehospital and mass casualty trauma care to generate 81 high priority research questions to guide future research and funding in this domain.Supplemental digital content is available in the text.